Iliopsoas abscess and adverse reactions to metal debris in the setting of an infected metal-on-metal hip arthroplasty. A case series - David O'Sullivan; Mark Curtin; Shane P. Russell; Colin G. Murphy (Journal of Orthopaedic Reports)
Background: A prosthetic joint infection is a devasting diagnosis and challenging condition to treat. The aim of this study is to outline the investigations, management and outcomes in a series of patients who presented to our institution with an iliopsoas abscess (IPA) in the setting of an infected, metal-on-metal (MoM), hip arthroplasty. Case details: Six patients with an IPA associated with an ipsilateral MoM presented over four years. Medical history, serum markers, trimodal imaging, aspirations and surgical procedures performed were analysed The management algorithm employed is outlined.Five were diagnosed with culture positive prosthetic joint infections (PJI). Four patients had elevated Cobalt and Chromium levels and all patients had characteristic aseptic lymphocytic vasculitis (ALVAL) associated lesions on Magnetic Resonance Imaging. Four proceeded to two stage revision. One patient opted for lifelong antibiotic suppression therapy. Four patients who opted for revision surgery had an infection free survival at mean 6 years. Conclusions: Our case series describes a rare, but significant consideration in the practice of the modern arthroplasty surgeon and a successful management strategy to treat these cases. Surgeons should be mindful of the potential concurrent presence of a PJI in cases of an IPA in the context of a total hip replacement, but especially for MoM, where concomitant malignancy, ALVAL, and metallosis are frequently implicated.